Degradasi Zat Warna Remazol Yellow Fg dengan Metode Fotosonolisis - Fauziah Rahma Yasin; Hary Sanjaya (Departemen Kimia FMIPA UNP, 2020)
This research was conducted on the degradation of Remazol Yellow FG by using the photosonolysis method with the aim of determining the optimum time and the amount of TiO2 used to doping optimum ZnO in degrading Remazol Yellow FG dyes. The degradation percentage results obtained from the absorbance value measured using UV-Vis Spectrophotometer. (Λmaks) Remazol Yellow FG obtained from UV-Vis spectrophotometer measurements were 415 nm. The results showed that the optimum irradiation and sonication time to degrade Remazol Yellow FG was 60 minutes with a degradation percentage of 74.24%. The effect of variations in the amount of TiO2 doping showed optimum results at 20% ZnO-TiO2, with a degradation percentage of 80.54%. The XRD analysis results obtained ZnO, TiO2 and ZnO-TiO2 crystal sizes respectively 48.50-80.70 nm, 48.96-83.81 nm and 48.57-96.58 nm. UV-DRS analysis obtained band gap values respectively 3.36 eV, 3.22 eV and 3.11 eV